'Internationales Treffen der Veteranen und Freunde der SAJ/SJD - Die Falken - OV Emden und der AJC Groningen. Emden 9 en 10 februari 1985'
'Internationales Treffen der Veteranen und Freunde der SAJ/SJD - Die Falken - OV Emden und der AJC Groningen. Emden 9 en 10 februari 1985'.